2015
DOI: 10.1021/jm500868e
|View full text |Cite
|
Sign up to set email alerts
|

(Dis)similar Analogues of Riboswitch Metabolites as Antibacterial Lead Compounds

Abstract: The rise of antimicrobial resistance in human pathogenic bacteria has increased the necessity for the discovery of novel, yet unexplored antibacterial drug targets. Riboswitches, which are embedded in untranslated regions of bacterial messenger RNA (mRNA), represent such an interesting target structure. These RNA elements regulate gene expression upon binding to natural metabolites, second messengers, and inorganic ions, such as fluoride with high affinity and in a highly discriminative manner. Recently, effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…Similar RNA switch motifs have been discovered in over 10 other flavi‐ and picornaviruses, however, none of which rise to a level of threat as a human pathogen comparable to HCV. Outside viruses, comparable deeply encapsulating ligand binding pockets in RNA are found in bacterial riboswitches which are being exploited as targets for antibiotics discovery …”
Section: Resultsmentioning
confidence: 99%
“…Similar RNA switch motifs have been discovered in over 10 other flavi‐ and picornaviruses, however, none of which rise to a level of threat as a human pathogen comparable to HCV. Outside viruses, comparable deeply encapsulating ligand binding pockets in RNA are found in bacterial riboswitches which are being exploited as targets for antibiotics discovery …”
Section: Resultsmentioning
confidence: 99%
“…Small molecules that are structurally dissimilar to the natural ligand but which mimic its activity to selectively downregulate riboswitchcontrolled biosynthetic genes essential for growth (herein referred to as a synthetic mimic) could serve as mechanistically novel therapeutic agents [7][8][9][10][11][12] . Riboflavin (vitamin B 2 ) biosynthesis serves as one potentially attractive metabolic pathway to apply this strategy in antibacterial discovery [11][12][13][14] .…”
mentioning
confidence: 99%
“…Therefore, disrupting riboflavin biosynthesis either by synthetic mimics of FMN or enzyme inhibitors of the pathway represents a novel target for antibacterial intervention with limited predicted off-target effects. To date, little success has been achieved in identifying synthetic mimics of riboswitch ligands despite using a variety of in vitro screening strategies, including affinity-based or fragment-based screening, or structure-guided design approaches starting with natural ligands [7][8][9] . One of the best-characterized antimetabolite inhibitors to a riboswitch is roseoflavin 17 , a naturally-produced analogue of riboflavin, which targets FMN riboswitches from multiple bacterial species 11,13,18,19 .…”
mentioning
confidence: 99%
“…Meanwhile, a number of antibacterial small molecule inhibitors was identified that mimic the natural ligands and influence riboswitch-controlled functions by binding selectively to the corresponding riboswitch. Some of the most potent compounds silence essential genes of bacteria, which respond to lysine, glucosamine-6-phosphate (GlcN6P), purine, cyclic-di-GMP, flavin mononucleotide (FMN) and thiamine pyrophosphate (Lünse et al, 2014; Matzner and Mayer, 2015; Schüller et al, 2016). Approaches using synthetic mimics of the natural ligands further demonstrated that riboswitches are druggable by synthetic chemistry (Howe et al, 2015).…”
Section: Regulatory and Sensory Rnas As Valuable Drug Targetsmentioning
confidence: 99%